(untitled) (World Science, 2021)
Tornadoes and strong squalls are dangerous for almost all spheres of human life and the economy of the region. The degree of negative impact depends on their type, quantity, intensity, area of formation and geographical features of the territory. The article defines the dynamics of the number of tornadoes and strong squalls in the North-Western Black Sea region (Odessa, Nikolayev and Kherson regions of Ukraine) from 2006 to 2020. Geographical position of the south-west of Ukraine, synoptic processes and a variety of climatic conditions contribute to the frequent occurrence of severe convective phenomena and creating the extraordinary complexity of their space-time distribution. The study revealed current trends in the formation of dangerous convective phenomena in the south-west of Ukraine. One of the most squall-prone regions of Ukraine is the territory of the North-Western Black Sea region. During 2006-2020 there was an increase in the number of squalls and tornadoes in the North-Western Black Sea region in comparison with previous years.